KONSEP PENDIDIKAN AKHLAK BAGI REMAJA(STUDI KOMPARASI KITAB TAISIRUL KHOLAQ DAN AKHLAKUL LIL BANIN) - Nanda Husna Ashfia An Nur; Ilman Nafia; Suklani (CV. ADIBA AISHA AMIRA, 2024)
Moral education has a very important role in forming adolescents who are qualified intellectually and behaviorally, have a character that has charisma and become human beings who are hablumminallah and hablumminannas. Adolescents at the age of 12 – 17 are an age group that is vulnerable to negative influences. These negative influences are usually obtained from the environment through the family environment, school environment and social environment with friends, and And also from the influence of social media especially living in an all-digital age. In today's era, technological development has a huge impact, both positive and negative impacts. It is undeniable that education that occurs in Indonesia is experiencing moral decay in studying because the character taught is minus the value of faith and manners. The phenomenon of moral decay is evident, such as promiscuity, crime among adolescents to children, violence, fraud and various other dishonorable acts. Therefore, it is necessary to instill moral education for adolescents, support systems from their environment. This research uses qualitative methods while the type of research used is a literature study. The purpose of this study is to analyze the concept of moral education for adolescents contained in the books of taisirul kholaq and akhlakul lil banin and their relevance to the moral degradation of adolescents. The results of this study show that in the book of taisirul kholaq and akhlakul lil banin there are several concepts of moral education for adolescents including morals towards the creator (Allah SWT), morals towards the Prophet Saw, morals towards both parents, Morals towards relatives, neighbors and some morals of getting along with fellow humans include having the nature of tawadhu, patient and kind to others, telling the truth. As for the relevance to the moral degradation of adolescents today, the two books are still relevant to be a guide in fostering, guiding adolescents even though it looks small, but the content conveyed by the muallif is very deep, firm and directed.